Adjunctive Perampanel Oral Suspension in Pediatric Patients From ≥2 to <12 Years of Age With Epilepsy: Pharmacokinetics, Safety, Tolerability, and Efficacy. (April 2019) - Renfroe, J. Ben; Mintz, Mark; Davis, Ronald; Ferreira, Jose; Dispoto, Sharon; Ferry, Jim; Umetsu, Yuko; Rege, Bhaskar; Majid, Oneeb; Hussein, Ziad; Laurenza, Antonio
Study 232, an open-label pilot study with an extension phase, evaluated the pharmacokinetics and preliminary safety/tolerability and efficacy of adjunctive perampanel oral suspension (≤0.18 mg/kg/d) in epilepsy patients aged ≥2 to <12 years. Patients were grouped into cohorts 1 (aged ≥7 to <12 years) and 2 (aged ≥2 to <7 years). The Core Study included pretreatment (≤2 weeks) and treatment phases (7-week titration; 4-week maintenance; 4-week follow-up [for those not entering the extension]). The extension phase consisted of 41-week maintenance and 4-week follow-up periods. Pharmacokinetic data were pooled with adolescent pharmacokinetic data from phase II/III studies. Population pharmacokinetic analysis showed that perampanel pharmacokinetics was independent of age, weight, or liver function, suggesting age- or weight-based dosing is not required and that the same dose can be given to adults and children to achieve exposures shown to be efficacious. Perampanel was well tolerated and efficacious for ≤52 weeks.